Screening for High-Yielding Pyruvate and Acetaldehyde Yeasts and Their Application in Improving the Stability of Anthocyanin in Mulberry Wine - Hui Zhou; Yajie Chai; Weidong Huang; Jicheng Zhan; Yilin You (Foods)
The structure of anthocyanins in mulberry wine is highly unstable and, therefore, degrades during the fermentation and aging process. This instability hinders the maintenance of color, affects the sensory quality, and impedes the development of the mulberry wine industry. In this study, high-yielding acetaldehyde yeasts Saccharomyces cerevisiae GS32 and Candida glabrata GS13, as well as high-yielding pyruvate yeast Candida xestobii D1, were selected from our laboratory’s strain bank for application in mulberry wine fermentation. The objective was to determine the impact of these high-yielding yeasts on improving anthocyanin content and color stability. The results revealed that different strains and inoculation methods significantly influenced anthocyanin content and color stability in mulberry wine. The GS32 exhibited the highest increase in total anthocyanin content, while the D1 showed a superior retention rate for C3G (a specific type of anthocyanin). Over a period of 1–5 weeks of aging time, minimal changes in color were observed across all treatment groups. These findings suggest that fermenting with yeast strains that yield high levels of pyruvate and acetaldehyde is an effective approach to address issues related to the poor stability of anthocyanins in mulberry wine.